STUDY OF ADSORPTION PHYSICS FOR HANDLING ENVIRONMENTAL POLLUTION - AN APPROACH TO THE PROBLEM BY ACADEMIC AND INDUSTRY COLLABORATION - Eiji Ishizaki, Atsushi Minato, Masanori Itaba and Satoru Ozawa, (International Journal of Research Science and Management, 2015)
Because of worldwide rapid development of industries, environmental pollution has now become a global problem. One of the techniques of handling the environmental pollution is development of adsorbent that removes contaminants from the polluted air, water and soil. This paper describes academic industry collaboration for developing an efficient adsorbent and its reverent system for the radioactive decontamination of Fukushima nuclear plant accident 2011. The Fukushima radioactive contamination occurred suddenly and unexpectedly by the nuclear plant accident which was triggered by the tsunami attack. The point was how to develop and supply a useful adsorbent in such an urgent situation. The lessons learned from the experience of the accident are summarized and some conclusive remarks are deduced regarding the study of adsorption physics for handling environmental pollution.